2014
DOI: 10.1002/fam.2283
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characteristics of foamed gel for mine fire control

Abstract: SUMMARYFoamed gel as a new type of fire extinguishing material is used to prevent the spontaneous combustion of coal. In order to make a comprehensive study on rheological characteristics of foamed gel for mine fire control, by using type NDJ-5s digital viscometer, the factors such as mass concentration of the mixture mixed by thickener and crosslinker, foaming multiple, added salts (NaCl, CaCl 2 , AlCl 3 ), pH value and temperature having influences on the rheological properties of foamed gel have been invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…It was shown that 0.4% foaming agent, 0.3% thickener and 0.3% crosslinking agent could obtain a foam gel with high foaming ratio, strong stability and good fire resistance (Figure 14). Subsequently, at this concentration, the effects of the foaming ratio, addition of salts (NaCl, CaCl 2 and AlCl 3 ), pH value and temperature on the rheological properties of the foam gel were discussed [60]. The fire extinguishing time of thickening agent and crosslinking agent mixture at different concentrations was also examined [61].…”
Section: Polymer-containing Soft Matters For Coal Mine Disaster/hamentioning
confidence: 99%
“…It was shown that 0.4% foaming agent, 0.3% thickener and 0.3% crosslinking agent could obtain a foam gel with high foaming ratio, strong stability and good fire resistance (Figure 14). Subsequently, at this concentration, the effects of the foaming ratio, addition of salts (NaCl, CaCl 2 and AlCl 3 ), pH value and temperature on the rheological properties of the foam gel were discussed [60]. The fire extinguishing time of thickening agent and crosslinking agent mixture at different concentrations was also examined [61].…”
Section: Polymer-containing Soft Matters For Coal Mine Disaster/hamentioning
confidence: 99%
“…After gelation, the bubbles are firmly trapped in the high viscosity gel film, which improves the elastic force and heat absorption ability of the foam, and can effectively reduce the flow of oxygen in goaf. After covering the coal body, a dense film can be formed on the surface of the foam body to permanently isolate oxygen, cover the high temperature fire source, and keep the surface of floating coal moist and prevent spontaneous combustion [8][9][10]. The theoretical and technical research on gel foam belongs to the research content of a new discipline, whose research results can effectively prevent coal spontaneous combustion and have very important theoretical and practical significance for ensuring safe mining in mines and constructing harmonious mining areas.…”
Section: Introductionmentioning
confidence: 99%
“…Low-temperature oxidation of coal has been extensively studied. [10][11][12][13][14][15][16][17][18] Thermogravimetric analysis is an effective technique for investigating the oxidation characteristics of coal. Zhu et al 14 studied some characteristic temperatures during coal spontaneous combustion by TG.…”
Section: Introductionmentioning
confidence: 99%
“…Low‐temperature oxidation of coal has been extensively studied 10‐18 . Thermogravimetric analysis is an effective technique for investigating the oxidation characteristics of coal.…”
Section: Introductionmentioning
confidence: 99%